2017
DOI: 10.1007/s00702-017-1759-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of motor events in REM sleep behavior disorder

Abstract: We used video-polysomnography to characterize motor events (ME) in 14 Parkinson's disease (PD-RBD) and 18 idiopathic (iRBD) REM sleep behavior disorder cases. ME occurred predominantly in the upper limbs and were mostly simple, non-emotional, distal and focal. There were no significant differences in ME features between PD-RBD and iRBD groups. Our data suggests that RBD ME are mostly non violent. Similarity between PD-RBD and iRBD groups suggests that motor dysfunction does not affect ME features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…This confirms previous findings by our own group using the same methodology, which had suggested a higher number of ME in patients with iRBD compared to those with PD and DLB who have RBD. 12 We may interpret these findings in a number of ways, one being that motor dysfunction or the consequences of more advanced neurodegeneration could diminish ME in PD and DLB cases (which would in turn contradict the hypothesis of motor restoration during REM sleep proposed by some studies 9,11,34 ). Another hypothesis would be a referral bias, causing more severe cases to arise from the iRBD group, as these patients would be referred to PSG mainly because of complaints directly connected with the parasomnia, whereas in other groups most patients would be referred to PSG for other complaints or in the course of disease follow-up procedures.…”
Section: Differences Related To Diagnostic Categorymentioning
confidence: 91%
See 2 more Smart Citations
“…This confirms previous findings by our own group using the same methodology, which had suggested a higher number of ME in patients with iRBD compared to those with PD and DLB who have RBD. 12 We may interpret these findings in a number of ways, one being that motor dysfunction or the consequences of more advanced neurodegeneration could diminish ME in PD and DLB cases (which would in turn contradict the hypothesis of motor restoration during REM sleep proposed by some studies 9,11,34 ). Another hypothesis would be a referral bias, causing more severe cases to arise from the iRBD group, as these patients would be referred to PSG mainly because of complaints directly connected with the parasomnia, whereas in other groups most patients would be referred to PSG for other complaints or in the course of disease follow-up procedures.…”
Section: Differences Related To Diagnostic Categorymentioning
confidence: 91%
“…Debate remains as to whether motor manifestations of RBD differ between patients with iRBD and RBD who fulfill criteria for an overt α-synucleinopathy such as PD, LBD and MSA (usually referred as secondary RBD, or sRBD). Although some studies have found motor events in patients with iRBD, those with PD with RBD, 9,11 and those with narcolepsy 11 to be similar, others have suggested that motor events frequency and severity could be worse in patients with iRBD than with sRBD. 12 Regarding sex predominance, epidemiological studies (some using validated questionnaires, 13 others based on the detection of REM sleep without atonia in patients with suggestive symptoms 7 ) differ from case studies, [14][15][16] showing an even percentage of female and male cases.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Whilst accounts of individuals kicking, punching, biting, or even strangling their bedpartners during sleep paint an emotive image of the condition and often capture public interest, they are prone to recall bias. More systematic studies have revealed that violent dreams and behaviors only make up a small percentage of all events (6)(7)(8). When a dream enactment is occurring, the individual's eyes will remain closed as they engage with the dream environment and their movements are generally contained to their immediate surroundings, thus differentiating these episodes from NREM parasomnias such as sleepwalking (4).…”
Section: Symptoms and Diagnostic Considerationsmentioning
confidence: 99%
“…The sample was mixed, as some patients had idiopathic RBD and others had RBD associated with Parkinson’s disease. Bugalho et al 30 found no difference in the frequency and pattern of motor events (including negative and positive emotional behaviours) during REM sleep on videopolysomnography in 14 patients with Parkinson's disease and RBD (all treated with dopaminergic drugs) vs. 18 patients with idiopathic RBD (not treated with dopaminergic drugs), suggesting that Parkinson's disease and treatment with dopaminergic agents have no major impact on the behaviours of patients with RBD. Eventually, the research was focused on the EOG correlates of emotions during REM sleep, whatever the dreaming content and its influences (previous day experiences, mood, drugs…).…”
Section: Discussionmentioning
confidence: 99%